2016
DOI: 10.3906/vet-1507-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of packaging method and dietary vitamin D3 supplementation on the quality of beef in rectus femoris, gluteus medius, and adductor femoris beef muscles

Abstract: The goal of the study was to assess the impact of packaging methods and doses of vitamin D 3 fed to animals (with feed) in the last days of finishing on selected indicators of beef quality. The parameters studied include the measurement of CIE L*, a*, and b* colour spaces and the Warner-Bratzler shear force. The muscles used in the study were the m. rectus femoris, m. gluteus medius, and m. adductor femoris, which were packed in two variants of modified atmosphere (MAP1, 80% O 2 :20% CO 2 and MAP2, 60% O 2 :40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Montgomery et al ( 26 ) and Caragney et al ( 3 , 4 ) have demonstrated an increase in the extent of protein degradation, especially troponin-T and other proteins responsible for the sarcomere integrity due to enhanced action of calcium-dependent proteases m- and However, the μ-calpain. However, the vitamin D 3 addition can affect negatively colour parameters, mainly reduce lightness ( 21 ). However, this relationship is not confirmed by Hansen et al ( 13 ) and Lobo-Jr et al ( 22 ).…”
Section: Improvement Of Beef Tenderness Using Vitamin D 3 mentioning
confidence: 99%
“…Montgomery et al ( 26 ) and Caragney et al ( 3 , 4 ) have demonstrated an increase in the extent of protein degradation, especially troponin-T and other proteins responsible for the sarcomere integrity due to enhanced action of calcium-dependent proteases m- and However, the μ-calpain. However, the vitamin D 3 addition can affect negatively colour parameters, mainly reduce lightness ( 21 ). However, this relationship is not confirmed by Hansen et al ( 13 ) and Lobo-Jr et al ( 22 ).…”
Section: Improvement Of Beef Tenderness Using Vitamin D 3 mentioning
confidence: 99%